SOCIAL ANALYSIS OF IMAM AL-BUKHARI’S WORK “AL-ADAB AL-MUFRAD” - Khudoyberdiyev Rashid Zokir o‘g‘li; Bekmurodova Sohiba Sultonmurod qizi (Web of Journals Publishing, 2025)
This article analyzes the concepts of social morality and etiquette through the hadiths presented in Imam al-Bukhari’s work Al-Adab al-Mufrad. The book frequently addresses concepts related to social responsibilities, including respect for parents, neighborly relations, compassion, justice, kindness, and social upbringing. The study applies a literary-analytical method (textual study of the book), examining the hadith texts and their social meanings. The article shows the role of Al-Adab al-Mufrad in shaping social harmony, moral communication among people, and the culture of etiquette. The conclusion provides the significance of the work for modern society and practical recommendations.
Keywords: Al-Adab al-Mufrad, morality, etiquette, social analysis, hadith, society.